Remote asymmetric induction via a chiral acetylene equivalent - Abel-Snape, Xavier; Jans, Clara; Mirabi, Bijan; Klischan, Moritz K. T.; Melder, Julian J.; Peloewetse, Atang; Hughes, Gregory J.; Lautens, Mark (ACS catalysis, 2025)
Asymmetric transformations have, to date, typically relied on proximal steric biasing to favor the formation of one enantiomer over the other during the enantiodetermining step. We report the use of an enantioenriched oxabicycle that serves both as a chiral auxiliary and an acetylene surrogate following two selective palladium-catalyzed carbopalladations and a postcatalytic retro-Diels-Alder step. Differentiating functional groups, that are remote from the reactive alkene, direct the reaction with an ortho-iodostyrene and a terminating reagent in a domino fashion, providing enantioenriched indenes. The phosphine ligand has a dramatic influence on the overall process, as alkyl- and arylphosphines lead to opposite major enantiomers of the final indene product.
Gesehen am 08.12.2025